FAKTOR-FAKTOR YANG MEMPENGARUHI PEMANFAATAN PUSAT INFORMASI DAN KONSELING-MAHASISWA (PIK-M) DALAM KESEHATAN REPRODUKSI REMAJA DI MASA PANDEMI COVID 19 - Ni Putu Widarini; Desak Nyoman Widyanthini; Nyoman Tri Maryanthi (JURNAL KESEHATAN REPRODUKSI, 2024)
Factors Influencing the Utilization of Information Center and Student Counseling (PIK-M) in Adolescent Reproductive Health during The Covid 19 Pandemic Background: During the COVID-19 pandemic, the Student Information and Counselling Center (PIK-M) faced restrictions in their operations. Despite this, it remained crucial for students to have continued access to reproductive health services. Objective: Examining the factors that influence the use of PIK-M in adolescent reproductive health during COVID-19 pandemic. Method: Quantitative research was conducted through a survey of 227 students selected by convenience sampling. The research was conducted at Poltekkes Kemenkes Denpasar in June–July 2021. Data collection was done using online questionnaires. Data were analyzed using descriptive univariable analysis, bivariable analysis employing Simple Linear Regression tests, and multivariable analysis utilizing Multiple Linear Regression. Result: Utilization of PIK-M during the pandemic was only 7.9%. Variables related to the use of PIK-M were self-confidence, facilities, commitment to action, support from PIK-M members, and PIK-M service satisfaction (p 0.05). Conclusion: There are limitations and obstacles to the implementation of PIK-M, so it requires a strategy for the sustainability of activities in pandemic times with increased creativity and the use of technology, as well as training and refreshment for the managers of PIP-M to strengthen the activities of PIK-M.